SUBORDINASI MAKNA ANTARA AMELIORASI DENGAN PEYORASI DALAM TEKS FLYER - zulfatun anisah (Institut Agama Islam Sunan Giri Bojonegoro, 2022)
The meaning of a word depends on the user of the language itself. In known words there are words that have a higher value and a lower value. The existence of this unequal meaning is known as subordinate. Words that increase in value are called amelioration, while words that decrease in value are called pejorations. I found this amelioration and preference in a flier, which reads a man's success in a career must have a woman behind him, namely his partner. And the destruction of a man must also have a woman behind him, namely his mistress. There are inaccuracies in the use and placement of words. The words that the writer highlights are the words male and female as amelioration, and the words male, female as peyorasi. In analyzing the researchers used a conceptual approach, because there was a change in the concept, and the technique used was a dressing technique. Through the technique of replacing the replaced element, it is always an element that is the main concern in the analysis. So that the results of improving the flier sentence become a man's success in a career must have a woman behind him, namely his partner. And the destruction of a man must also have a woman behind him, namely his mistress.